Moravská identita a její nové dimenze - Roman Iščuk (AntropoWebzin)
The theme is crucial to the concrete question, whether moravian identity really exists. It´s about phenomena which is natural and important for some parts of population or on the other hand we can see this identity as the artificial problem. The main goal is connecting with results from the field work. I would like to explain something about moravian political elites according to the non-political activism. It´s also necessary to mark historical processes which are important for present time. The polemic should have done some reflexive view on regionalism, activation of moravian elites and civic movements.